Biochemical effects of Nigella sativa seeds in diabetic rats - Ahmed, Qamar Uddin (National Institute of Science Communication and Information Resources (NISCAIR), India., 2006)
Oral administration of ethanol extract of N. sativa seeds (300 mg/kg body weight/day) to streptozotocin induced diabetic rats for 30 days significantly reduced the elevated levels of blood glucose, lipids, plasma insulin and improved altered levels of lipid peroxidation products (TBARS and hydroperoxides) and antioxidant enzymes like catalase, superoxide dismutase, reduced glutathione and glutathione peroxidase in liver and kidney. The results confirm the antidiabetic activity of N. sativa seeds extract and suggest that because of its antioxidant effects its administration may be useful in controlling the diabetic complications in experimental diabetic rats.